MELACAK KEASLIAN NASKAH PERJANJIAN PERDAMAIAN NAJRAN: : Studi Filologi Manuskrip sebelum abad IV H. - Abdurrahman Abdurrahman (LP3M IAI Al-Qolam, 2020)
The Peace Agreement for the Najran Residents was made around 9 AH, later than other more popular manuscripts, namely the Hudaibiyah Agreement in 6 AH, and even the Medina Charter in 1 AH. However, the authenticity of the Najran Agreement is still questionable by some circles. As a manuscript that is related to important event and is narrated in the Al-Qur'an, it is very important to trace its authenticity. In order to explore it, this research uses the method of of philology, with the approach of textological and cadric studies. This method is used to trace old manuscripts before 4th century H. The result shows that 8 manuscripts were found between the early II century H to the end of the III century H. One of which is the work of Muhammad bin Al-Hasan As-Syaibani, printed in 1975 AD. Critical tectological analysis found 2 irregularities in the Master Text and 9 differences between the Master Text and other texts. This leads to the revision of the Master Text as the closest description to the original text. Meanwhile, a cadicological study of the Master Manuscript gave birth to the findings of 6 convincing evidences of the authenticity of the Manuscript of the Agreement.